Conformational Changes in Low Molecular Weight Kininogen Alters Its Ability to Bind to Endothelial Cells - Hasan, Ahmed A K; Zhang, Jie; Samuel, Mathew; Schmaier, Alvin H (Thrombosis and Haemostasis, 1995)
The plasma kininogens, high (HK) and low (LK) molecular weight kininogens, are the parent proteins for bradykinin, a potent vasoactive peptide that locally influences vascular biology. Binding of both HK and LK to the endovascular wall contributes to bradykinin delivery. Recently, we found one preparation of LK (LKd) which had reduced inhibition of biotin-HK binding to endothelium. The functional defect in LKd was not merely due to bradykinin loss because two preparations of bradykinin-free LK blocked biotin-HK binding. However, using two different particular monoclonal antibodies to bradykinin, LKd, but no other preparation of LK, had its epitope to bradykinin exposed on nonreduced samples on immunoblot. These data suggested that LKd had an altered conformation which exposed the amino terminal arginine of bradykinin to antigenic detection. The altered conformation of LKd allowed it to be more susceptible to trypsin proteolysis. On circular dichroism, the percentage of α-helix was significantly increased, indicating an alteration in the protein. This alteration in LKd was not due to a loss of molecular mass of the protein. On laser desorption mass spectroscopy, the molecular mass of LKd was similar to the other preparations of LK. Investigations were performed to ascertain the mechanism by which LKd had altered ability to bind to cells. LKd was found to be proteolyzed by an unknown protease at the beginning of domain 2 between threonine119and alanine120. Reduction of functional LK with dithiothreitol to expose its bradykinin epitope did not produce the LKd defect. Proteolysis of functional LK with plasma kallikrein, elastase followed by plasma kallikrein, chymotrypsin, or bromelain also did not produce the defect seen in LKd. These combined data indicated that LK maintains a particular conformation that allows the protein to orient itself such that it can bind to endothelial cells. Proteolysis in the surface exposed region between domains 1 and 2 probably allows for the protein to unfold and contributes to its lost ability to bind to endothelial cells.